ریاست مدینہ کے کے فلاحی تصورات اور اسلامی جمہوریہ پاکستان : اطلاقی جائزہ: Welfare Concepts of Madina State and Islamic Republic of Pakistan : Applied review - Dr. Sana Ullah; Saeed Ul Haq (MEI, 2023)
The welfare of Humanity is the basic concept of Islam; therefore, The Prophet (SAW) described the golden principles for welfare of humanity in the whole institutions of the state and used it in the welfare stae of Madina, which is unique example for the all states of the world. Prophet (SAW) allotted plats to the poor people and established educational instutitions and gave free education.He controlled the high prices. He established….. and owned the merit policy in Madina state.He made peace and owned simplicity in the Madina society. He also established the system of Zakat and taxation and built mosques.he governed best economic policy, and interst was forbidden. He manage for women education. These were important points wich were made and utilized by prophet(SAW) in the state of madina. Pakistan is an Islmic State and currently government is making its efforts to follow the principles of madina state. In this paper consept of welfare state of Madina is discussed and its degree of applieation in islamic Republic of Pakistan is carried out.